Ramped pyroxidation: A new approach for radiocarbon dating of lime mortars. (May 2021) - Barrett, Gerard Thomas; Keaveney, Evelyn; Lindroos, Alf; Donnelly, Colm; Daugbjerg, Thomas Schrøder; Ringbom, Åsa; Olsen, Jesper; Reimer, Paula J.
Abstract: Current methodologies for radiocarbon dating of mortars typically use mechanical and chemical separation to isolate fractions of carbon dioxide from suitable lime binder carbonates. These methods have a moderate frequency of success, but difficulties are often encountered with (a) secondary crystallisation, (b) the presence of incompletely burnt limestone or limestone aggregate, and (c) more complex hydraulic mortars (e.g. pozzolana or cocciopesto mortars). An alternative approach to isolating CO2 from mortar involves thermal decomposition of the sample. A new ramped pyroxidation (RPO) facility has recently been constructed at the 14 CHRONO Centre. In RPO, samples are incrementally heated, with CO2 produced as the sample undergoes thermal decomposition in the presence (oxidation) or absence (pyrolysis) of oxygen. The CO2 evolved from different temperature fraction are collected cryogenically and radiocarbon dated. This method was applied to several lime mortars with expected ages to investigate if CO2 fractions only associated with the setting of the lime binder could be isolated. For all samples tested, positive results were obtained. All but the first of six CO2 fraction taken during the earlier stages of thermal decomposition were in statistical agreement and could be combined to provide an age that was in excellent agreement with the expected ages (for an Irish medieval round tower, and for a Finnish medieval castle and church). The lowest temperature fraction, not in statistical agreement, is significantly earlier and attributed to contamination from charcoal or coke from lime production. Positive results were also obtained from a piece of mortar that had undergone no pre-treatment. Modelling examining the potential of RPO to isolate lime binder CO2 fractions, where either limestone (or incompletely burnt limestone) or secondary re-crystallised calcite are present as contaminants, further demonstrate the suitability of the approach. Highlights: Application of ramped pyroxidation to mortar radiocarbon dating. Excellent agreement between age estimates and expected ages. Positive results on material without pre-treatment. Models highlight the suitability of the method.